1994
DOI: 10.1212/wnl.44.10.1944
|View full text |Cite
|
Sign up to set email alerts
|

MRI monitoring of vigabatrin‐induced intramyelinic edema in dogs

Abstract: Chronic administration of vigabatrin (gamma-vinyl GABA) in dogs produces reversible microvacuolation (intramyelinic edema) in discrete brain regions. Histologic changes are most notable in the columns of the fornix and regions of the hypothalamus, thalamus, optic tract, and hippocampus. In an attempt to image these changes in vivo, we performed high-field MRI on seven treated and four control dogs at baseline and after 15 weeks of dosing with vigabatrin (300 mg/kg/d). All dogs underwent parallel electrophysiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 0 publications
0
28
0
1
Order By: Relevance
“…Although the nucleus basalis is enriched in GABA-ergic input (47), we did not observe any abnormalities in this area in MR images or histologic sections. We speculate that VGB-induced toxicity is related to tissue-specific effects on the white matter (7,8). Axonal damage also might result from loss of normal interaction with oligodendrocytes.…”
Section: Discussionmentioning
confidence: 93%
“…Although the nucleus basalis is enriched in GABA-ergic input (47), we did not observe any abnormalities in this area in MR images or histologic sections. We speculate that VGB-induced toxicity is related to tissue-specific effects on the white matter (7,8). Axonal damage also might result from loss of normal interaction with oligodendrocytes.…”
Section: Discussionmentioning
confidence: 93%
“…However, significant differences based on group averages were not observed until 8-10 wk of dosing (32). MRI changes were also detectable after 4-7 wk (37). Thus, functional disturbances of the vigabatrin-treated dog brain appear to occur at about the same time or slightly after the intramyelinic edema becomes distinguishable from the background vacuolation of controls.…”
Section: Histopczthologymentioning
confidence: 84%
“…Toxicity studies with vigabatrin have demonstrated microscopic brain vacuolation, most notably in white matter tracts, as the main toxic effect in mice, rats, and dogs given dosages of 30-300 mg/ kg/day in subacute and chronic tests (1,4,5,9,10,32,37). Cynomolgus monkeys treated with 300 mg/ kg/day for 16 mo exhibited minimal microvacuolation, which was considered equivocal since it was not noticeably different from background observed in controls (4,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Increased signal on T,-weighted images and histologic changes of IME were closely correlated. In dogs, regions with IME demonstrated increased signal on T,-weighted images and decreased signal on T, -weighted images (16,48). The development of the T, signal abnormality followed the time-course and anatomic distribution of pathologic changes.…”
Section: Magnetic Resonance Imaging In Animalsmentioning
confidence: 92%